Probabilistic risk assessment of historic timber flooring systems subjected to fire - E. Garcia-Castillo; I. Paya-Zaforteza; T. Gernay (Developments in the Built Environment)
Structural fire analyses of historic buildings face significant uncertainties due to their age and the scarcity of specific fire safety guidelines in modern codes. Typical prescriptive approaches often result in interventions that compromise the aesthetic and cultural value of these structures. In contrast, probabilistic performance-based approaches address uncertainties and offer flexibility to achieve compliance with fire safety requirements while preserving built heritage.This study introduces a novel probabilistic methodology to assess the fire resistance of timber structures, demonstrated on historic timber jack arch flooring systems. Extensive numerical simulations were conducted to develop fire fragility functions and obtain reliability indices, incorporating variability in timber density, mechanical properties, strength reduction with temperature, and applied loads. Results indicate that many of the historic systems studied possess adequate fire safety. Applicable to any timber structure, this methodology allows case-specific analyses, promoting the rational conservation and design of heritage and contemporary timber systems.